Exploring the hepatic-ophthalmic axis through immune modulation and cellular dynamics in diabetic retinopathy and non-alcoholic fatty liver disease - Shuyan Zhang; Jiajun Wu; Leilei Wang; Cheng Zhang; Yinjian Zhang; Yibin Feng (Human Genomics)
Abstract Background Dysfunctions within the liver system are intricately linked to the progression of diabetic retinopathy (DR) and non-alcoholic fatty liver disease (NAFLD). This study leverages systematic analysis to elucidate the complex cross-talk and communication pathways among diverse cell populations implicated in the pathogenesis of DR and NAFLD. Methods Single-cell RNA sequencing data for proliferative diabetic retinopathy (PDR) and NAFLD were retrieved from the Gene Expression Omnibus (GEO) database. Differential gene expression analysis was conducted and followed by pseudo-time analysis to delineate dynamic changes in core cells and differentially expressed genes (DEGs). CellChat was employed to predict intercellular communication and signaling pathways. Additionally, gene set enrichment and variation analyses (GSEA and GSVA) were performed to uncover key functional enrichments. Results Our comparative analysis of the two datasets focused on T cells, macrophages and endothelial cells, revealing SYNE2 as a notable DEG. Notably, common genes including PYHIN1, SLC38A1, ETS1 (T cells), PPFIBP1, LIFR, HSPG2 (endothelial cells), and MSR1 (macrophages), emerged among the top 50 DEGs across these cell types. The CD45 signaling pathway was pivotal for T cells and macrophages, exerting profound effects on other cells in both PDR and NAFLD. Moreover, GSEA and GSVA underscored their involvement in cellular communication, immune modulation, energy metabolism, mitotic processes. Conclusion The comprehensive investigation of T cells, macrophages, endothelial cells, and the CD45 signaling pathway advances our understanding of the intricate biological processes underpinning DR and NAFLD. This research underscores the imperative of exploring immune-related cell interactions, shedding light on novel therapeutic avenues in these disease contexts.